Preoperative anxiety during COVID-19 pandemic: A single-center observational study and comparison with a historical cohort - Buonanno, Pasquale; Marra, Annachiara; Iacovazzo, Carmine; Vargas, Maria; Nappi, Serena; de Siena, Andrea Uriel; Servillo, Giuseppe (Frontiers in Medicine, 2022)
Background: Preoperative anxiety is a common sensation experienced by patients undergoing surgical interventions; it can influence intraoperative and postoperative management through the activation of neuroendocrine system. Anxiety is defined as a stress response to an unfocused threat, whereas fear is defined as the reaction to a specific danger; it is usually divided in state anxiety, a transitory emotional response, and trait anxiety, a stable psychological characteristic of the individual, describing the probability to feel anxious in a distressing situation. Our aim was to investigate the level of preoperative anxiety during COVID-19 pandemic; we also compared it to the preoperative anxiety of a historical cohort before the outbreak. Methods: This is a single-centre observational study. We enrolled 314 patients during pandemic; our historical cohort was made of 122 patients. Amsterdam Preoperative anxiety and Information Scale (APAIS) scale and State-Trait Anxiety Inventory (STAI) were used to evaluate preoperative anxiety: in particular, APAIS measures preoperative anxiety and need for information and STAI assesses state and trait anxiety through STAI-Y1 and STAI-Y2, respectively. We collected APAIS and STAI scores in our population stratified on the basis of age, gender, marital status, previous surgical experiences, and type of surgery. Results: Our results showed that state and preoperative anxiety remained stable, whereas trait anxiety increased in all the subgroups analysed. Discussion: Even if state anxiety is considered a variable characteristic of the emotional sphere and trait anxiety a stable element, our findings suggested that COVID-19 deeply influenced trait anxiety, thus altering the patients’ psychological foundations.